Commitment to self-rewards - Alexander K. Koch; Julia Nafziger (Institute for the Study of Labor (IZA), 2009)
Self-administered rewards are ubiquitous. They serve as incentives for personal accomplishments and are widely recommended as tools for overcoming self-control problems. However, it seems puzzling why self-rewards can work: the prospect of a reward has a motivating force only if the threat of self-denial of the reward after low performance is credible. We explain how a rational forward-looking individual may achieve commitment to self-rewards, by applying Köszegi and Rabin's (2006) model of endogenous reference point formation to a self-regulation problem. Our results show why and when self-regulation built on self-rewards can be successful and thus illustrate the power, but also the limits, of self-rewards.
urn:nbn:de:101:1-20090323189
Keywords: A12; C70; D86; 330; Self-control; motivation; self-reinforcement; time inconsistency; reference-dependent preferences; Motivation; Präferenztheorie; Willingness to pay; Eigeninteresse; Theorie